ATF3 Protects against LPS-Induced Inflammation in Mice via Inhibiting HMGB1 Expression. (26th August 2013) - Lai, Pei-Fang; Cheng, Ching-Feng; Lin, Heng; Tseng, Tzu-Ling; Chen, Hsi-Hsien; Chen, Sung-Ho
Abstract : Lipopolysaccharide (LPS) triggers innate immunity mainly via TLR4 signaling. ATF3 is a negative regulator of TLR4 signaling. HMGB1 plays a critical role in the final step of sepsis. However, the mechanisms of ATF3 and the role of HMGB1 in regulating innate immunity-induced sepsis are incompletely understood. In this study, we found that serum HMGB1 levels were 10-fold higher in patients with sepsis than normal controls. We further demonstrated that ATF3 gene knockout in mice subjected to LPS-induced endotoxemia correlates with an increase in the mortality rate and the elevated expression of IL-6, TNF- α, NO, MCP-1, and HMGB1 in the lung tissues or serum. The biochemical effects of ATF3 were observed in in vitro macrophages and blocked by ATF3 siRNA treatment. We have also shown that adeno-associated virus-mediated ATF3 gene transfer protected ATF3 knockout mice from LPS-induced mortality. In addition, ATF3 knockdown increased LPS-induced release of HMGB1. In conclusion, upregulation of ATF3 contributes to the reduced release of inflammatory molecules, especially HMGB1, which induced lung injury and increased the survival rate of mice after LPS challenge. Therefore, suppressing LPS-induced inflammation with ATF3 induction or ATF3 mimetics may be an important strategy for sepsis therapy.